LEARNER STRATEGIES FOR IMPROVING SPEAKING FLUENCY - MAMADJONOVA FERUZA (TADQIQOTLAR, 2025)
ABSTRACT   Speaking fluency is a vital component of effective communication and a key goal in language learning. Learners often face challenges such as hesitation, lack of vocabulary, limited confidence, and poor pronunciation, which hinder their fluency development. This study explores various learner strategies for improving speaking fluency, including self-monitoring, shadowing, repetition drills, interaction with peers, and  the  use  of  digital  tools.  It  also  highlights  the  role  of  motivation,  exposure  to authentic  materials,  and  consistent  practice  in  enhancing  fluency.  The  findings emphasize  that  adopting  a  combination  of  cognitive,  metacognitive,  and  socio-affective  strategies  can  significantly  improve  learners’  speaking  performance. Encouraging  autonomy,  promoting  meaningful  interaction,  and  integrating technology-based practices are shown to be effective in fostering fluency.